Cal Poly exhibit at Cow Palace (1960)
Three students look at the joint Cal Poly San Luis Obispo and Cal Poly Pomona exhibit at Cow Palace. Cal Poly would often send Animal and Dairy Husbandry majors to this event to compare weights, classifications, and sales of their animals.